The law of insurance warranties : an insoluble problem? - Owen, Alastair (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The book provides a detailed review of efforts to reform the law on insurance warranties in Australia, New Zealand and the UK, arguing that none of these have been successful. The text proposes a radical new approach to reform of this area of the law, demonstrating through detailed stress testing of these proposals that they would deliver more consistent and equitable outcomes than those achieved to date. Reform of the historically inequitable law of insurance warranties in commercial insurance has been introduced in Australia, New Zealand and, most recently, the UK. This book demonstrates that all these reforms have flaws and that none of them can be relied upon to deliver consistently equitable and predictable outcomes; in particular the UK's, as yet largely untested, Insurance Act 2015 is shown to have serious flaws that have not previously been identified. Building on lessons from these three jurisdictions, the book sets out an alternative approach for dealing with breaches of insurance warranties and demonstrates that this would consistently deliver better outcomes than any of the existing attempts at reforming this area of the law. Providing an unprecedented multi-jurisdictional review of the law on insurance warranties and in particular the treatment of warranties in the Insurance Act 2015, as well as outlining an innovative and radical alternative approach to reform, the book will be of considerable interest and value to practitioners, academics and students, as well as to other common law jurisdictions contemplating reform of this area of the law"--
The origin and history of insurance warranties -- The law in relation to warranties prior to the Insurance Act 2015 -- Implied warranties and the case for a separate regime for Marine Insurance -- The law commission's previous reports and recommendations on warranties -- The law on insurance warranties in Australia -- The law on insurance warranties in New Zealand -- The 2014 Law Commission Proposals -- The Insurance Act 2015 : an effective reform of the law on warranties and other provisions? -- Stress testing the regimes for insurance warranties in Australia, New Zealand and the UK -- Issues : problems with the law on warranties and potential solutions for resolving them -- A proposed solution.
OCLC-licensed vendor bibliographic record.
Keywords: Great Britain; Insurance law; Marine insurance -- Law and legislation; Warranty; Insurance law -- Great Britain; Warranty -- Great Britain; LAW / Commercial / General; LAW / Insurance